THE STORYTELLING STYLES AND BRAND PERCEPTION OF WINE LABELS - Immonen, Fana-Maria (My University, 2016)
Based on the past marketing research, it can be stated that stories play a significant role in influencing consumers, since story-based communication has been deemed more effective than stating mere facts (Kelley & Littman 2006). However, especially the link between brand perception and the storytelling of product labels is simply under-researched. (Charters et al. 2000; Kniazeva & Belk 2007.) Therefore, the purpose of this study was to investigate how storytelling on product labels effects consumers’ brand perception. The research questions wanted to discover: what storytelling styles and elements can be found on wine labels, how can the different storytelling elements of wine labels be interpreted/classified and how consumers perceive the stories told by wine label design styles. In order to answer the above-presented questions, methodologically this research was divided into three steps: literature review, content analysis and focus group interview, each step representing one sub-question. The first part contained the identification of different storytelling elements through a literature review. The second sub-question was aimed to group the different storytelling elements according to different wine label design styles by using a content analysis. During the third step, a focus group interview and content analysis were conducted in order to construct a brand experience table. The findings gathered throughout this thesis show that charismatic well-told stories are being characterised by the front label containing the brand name, the main image and the used colours, and the back label the food matching, description for tastes and smells, grape varietal, the colour choices as well as an explication for the brand name within the packaging narrative. This is true no matter the wine label design style. In addition, overall theme or the atmosphere of the main image together with the brand name on the front label play an essential role in determining the wine label design style. On the other hand, the wine label aims to communicate to the consumer, the sense of style of the wine, the occasion for use, the production technique as well as the relevant information about the tastes and the smells of the wine. These attributes are among the most important factors that influence consumers’ brand perception, interpretation of the wines style as well as the occasion for use. Based on the findings, it can be assumed that in order to establish the relationship between story-telling through wine labels and the consumers’ brand perception, the front label needs to set the tone and the atmosphere for the story that the back label helps to fortify, enliven and support. In other words, the front label can be understood as creating expectations that the back label not only needs to confirm but to enhance, support and further convince. As a general conclusion, it can be stated that, more the different elements form a well-design ensemble or the overall impression being congruent in style – in other words, the written and the non-written elements are in line with each other and coherent on both labels – more likely the consumers find the wine brand truthful and desirable, which in turn means that the consumers end up believing the story told by the wine labels.